Isolation and Characterization of Mutant Sinorhizobium meliloti NodD1 Proteins with Altered Responses to Luteolin - Peck, Melicent C. (American Society for Microbiology, 2013)
NodD1, a member of the NodD family of LysR-type transcriptional regulators (LTTRs), mediates nodulation (nod) gene expression in the soil bacterium Sinorhizobium meliloti in response to the plant-secreted flavonoid luteolin. We used genetic screens and targeted approaches to identify NodD1 residues that show altered responses to luteolin during the activation of nod gene transcription. Here we report four types of NodD1 mutants. Type I (NodD1 L69F, S104L, D134N, and M193I mutants) displays reduced or no activation of nod gene expression. Type II (NodD1 K205N) is constitutively active but repressed by luteolin. Type III (NodD1 L280F) demonstrates enhanced activity with luteolin compared to that of wild-type NodD1. Type IV (NodD1 D284N) shows moderate constitutive activity yet can still be induced by luteolin. In the absence of luteolin, many mutants display a low binding affinity for nod gene promoter DNA in vitro. Several mutants also show, as does wild-type NodD1, increased affinity for nod gene promoters with added luteolin. All of the NodD1 mutant proteins can homodimerize and heterodimerize with wild-type NodD1. Based on these data and the crystal structures of several LTTRs, we present a structural model of wild-type NodD1, identifying residues important for inducer binding, protein multimerization, and interaction with RNA polymerase at nod gene promoters.